Bridging risk and enactment: the role of psychology in leading psychosocial research to augment the public health approach to violence in South Africa - Bowman, Brett; Stevens, Garth; Eagle, Gillian; Maztopoulos, Richard (My University, 2014)
In the wake of apartheid, many in the South African health and social sciences shifted their orientation to understanding violence. Rather than approaching violence as a criminal problem, post-apartheid scholarship surfaced violence as a threat to national health. This re-orientation was well aligned with a global groundswell that culminated in the World Health Assembly’s 1996 declaration of violence as a public health problem. In response, researchers and other stakeholders have committed to the public health approach to violence in South Africa. Despite some unquestionable successes in applying this approach, violence remains a critical social issue and its recalcitrantly high rates signal that there is still much work to be done. One avenue for more focussed research concerns understanding the mechanisms by which upstream risk factors for violence are translated into actual enactments. We argue that South African psychology is well placed to provide greater resolution to this focus. We begin by providing a brief overview of the public health approach to violence. We then point to three specific areas in which the limits to our understanding of the way that downstream psychological and upstream social risk factors converge in situations of violence, compromise the theoretical and prevention traction promised by this approach and chart several basic psychosocial research coordinates for South African psychology. Steering future studies of violence by these coordinates would go some way to addressing these limits and, in so doing, extend on the substantial gains already yielded by the public health approach to violence in South Africa.
Keywords: Psychology; Psychosocial; Public health; South Africa; Violence